Sustainable Development Goals 2018
DOI: 10.4337/9781786438768.00008
|View full text |Cite
|
Sign up to set email alerts
|

The Sustainable Development Goals, anthropocentrism and neoliberalism

Abstract: The version presented here may differ from the published version or, version of record, if you wish to cite this item you are advised to consult the publisher's version. Please see the 'permanent WRAP URL' above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 9 publications
(9 reference statements)
1
54
0
Order By: Relevance
“…These include, for example, international environmental law's support of several foundational paradigms that underlie global economic, political, legal, and social human systems such as: anthropocentric sustainable development, (neo) colonialism, property rights, state sovereignty, and neoliberal corporate exploitation [30]. As I have shown elsewhere in some detail [30,31], international environmental law (mostly implicitly, but often also explicitly), structurally contributes to causing, sustaining, and exacerbating these predatory paradigms that, in turn, result in Earth system destruction, exploitation, and the oppression of vulnerable humans (mostly those situated in the Global South) and oppression of the non-human world (see also references [32,33]).…”
Section: International Environmental Law and The Anthropocenementioning
confidence: 99%
“…These include, for example, international environmental law's support of several foundational paradigms that underlie global economic, political, legal, and social human systems such as: anthropocentric sustainable development, (neo) colonialism, property rights, state sovereignty, and neoliberal corporate exploitation [30]. As I have shown elsewhere in some detail [30,31], international environmental law (mostly implicitly, but often also explicitly), structurally contributes to causing, sustaining, and exacerbating these predatory paradigms that, in turn, result in Earth system destruction, exploitation, and the oppression of vulnerable humans (mostly those situated in the Global South) and oppression of the non-human world (see also references [32,33]).…”
Section: International Environmental Law and The Anthropocenementioning
confidence: 99%
“…But as deceptively simple and environmentally oriented an idea as sustainable development seems to be, it is not a socio-ecologically friendly process. 30 Critical legal scholars have shown that it is rather a convenient, fictitious ideological palliative that IEL underwrites and that legitimizes and helps rationalize anthropocentric Earth system altering practices. 31 Other principles of IEL such as the polluter pays, prevention, and precautionary principles are more explicitly focused on achieving environmental protection results.…”
Section: Iel's Normative Ambition?mentioning
confidence: 99%
“…and States continue down the unambitious "sustainable development" path, which they fully endorsed at subsequent global conferences (such as the UN Conference on Environment and Development of 1992 and the World Summit on Sustainable Development in 2002), and through grand development visions such as Our Common Future of 1987, the Millennium Development Goals, and more recently, the Sustainable Development Goals 46. …”
mentioning
confidence: 99%
“…Commentators criticise the principle of SD for facilitating the prioritisation of economic development over environmental and social concerns. 10 By contrast, detractors of the HRHE fault the human rights approach to environmental protection for giving weight to the entitlement to a clean and healthy environment while downplaying the need for commensurate duties to care for nature. 11 In reference to relevant critical debates, this article explores how the principle of SD and the HRHE have taken shape in Kenya's legal context.…”
Section: Introductionmentioning
confidence: 99%